Changes in sports participation across transition to retirement: modification by migration background and acculturation status - Schönbach, Johanna-Katharina; Bombana, Manuela; Börnhorst, Claudia; Zeeb, Hajo; Brand, Tilman (International journal of environmental research and public health, 2017)
While total physical activity decreases over the life course, sports and leisure-time physical activity (LTPA) have shown to increase after transition to retirement. This paper aimed to investigate whether this change in sports participation differs (1) between non-migrant persons (NMP) versus persons with a migrant background (PMB), and (2) by acculturation status. Data was drawn from 16 waves of the German Socio-Economic Panel Study (SOEP) including 2664 NMP and 569 PMB. PMB were grouped according to acculturation status (integrated, assimilated, marginalised, separated), assessed regarding three dimensions (language, social interaction and identification). We applied multilevel logistic regression models, adjusting for sex, retirement age, socioeconomic status, health status and body mass index. Our results show that (1) transition to retirement led to an increase in the sports participation of NMP during the first 5 years and the subsequent 5 years after retirement. Changes in sports participation were modified by migration status: In PMB sports participation increased to a lesser extent than in NMP. (2) While sports participation of integrated PMB was not significantly different from NMP in the preretirement phase, sports participation among integrated PMB increased less after retirement compared with NMP. Marginalized and assimilated PMB did not show consistent sports participation patterns before retirement, but seemingly increased their sports participation less than NMP over the retirement transition. Separated PMB had particularly low levels of sports participation. Considering that LTPA is a key factor for healthy ageing, the increasing gap in levels of sports participation after transition to retirement indicates the need for interventions targeting physical activity of the older migrant population.